Chironomidae (Diptera) associado à Eichhornia azurea em seis lagoas marginais ao rio Paranapanema, SP - Araki, Natalia Kaori [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The family Chironomidae is one of the most important groups within the macroinvertebrate communities, both in density and in richness, and because of its high adaptive value, has a wide distribution on the planet. These and other more specific features of each genus allow the use of this group of biomonitoring studies in the aquatic ecosystem, however, primarily, it is necessary to inventory the aquatic fauna. Thus, this study aimed to evaluate the taxonomic composition of Chironomidae associated with Eichhornia azurea in six lateral lagoons of Paranapanema River, where only five of them have very little information about the aquatic fauna associated with floating macrophytes. Furthermore, we analyzed the influence of environmental conditions on the richness and density of this community. Samples (biotic and abiotic) were held in March and August 2009 on the Ivo, Carmo, Sete Ilhas, Barbosa, Poço da Pedra and Coqueiral lagoons, which are upstream of the Jurumirim Reservoir. Samples with an area of 0.1976 m2 were collected at three banks of E. azurea of each lagoon. Then, they were washed in formaldehyde and water and fixed in 70% alcohol. The identification of morphospecies recorded 38 taxa (32 in March and 37 in August), where the Ivo lagoon is the richest (27 taxa). The density of each group varied according to each pond and is generally Asheum sp., Chironomus sp., Beardius sp., Parachironomus sp., Labrundinia sp., Tanytarsus sp., Ablabesmyia sp. and Polypedilum sp. the most representative. Limnophyes sp., Denopelopia sp., Paratanytarsus sp. and Parametriocnemus sp. were genders in lower density. The Dominance index ranged between 0.1490 (Barbosa Lagoon in March) and 0.4114 (Poço da Pedra Lagoon in March), and the Diversity Index ranged from 2.08 (Coqueiral Lagoon in March) and 3.58 (Barbosa Lagoon in August). The concentration of dissolved oxygen and pH were the environmental variables most correlated with the groups ...

A família Chironomidae constitui um dos grupos mais importante dentro da comunidade de macroinvertebrados aquáticos, tanto em densidade quanto em riqueza, e devido ao seu alto valor adaptativo, possui ampla distribuição no planeta. Essas e outras características mais específicas de cada gênero possibilitam o uso deste grupo em estudos de biomonitoramento do ecossistema aquático, entretanto, a priori, é necessário inventariar esta fauna. Deste modo, este estudo teve como objetivo avaliar a composição taxonômica de Chironomidae associado à Eichhornia azurea de seis lagoas marginais ao rio Paranapanema, dentre as quais cinco delas possuem somente informação acerca da fauna aquática associada à mesma macrófita flutuante. Além disso, buscou-se analisar a influência das condições ambientais sobre a riqueza e densidade dessa comunidade. As amostragens (biótica e abiótica) foram realizadas em março e agosto de 2009, nas Lagoas do Ivo, Carmo, Sete Ilhas, Barbosa, Poço da Pedra e Coqueiral, que ficam a montante do Reservatório de Jurumirim. Amostras com área 0,1976 m2 foram coletadas em três bancos de E. azurea de cada lagoa; a seguir, foram lavadas em formol e água e fixadas em álcool 70%. Conforme a identificação dos morfogrupos foram registrados 38 taxa (32 em março e 37 em agosto), sendo a Lagoa do Ivo a mais rica em quironomídeos (27 taxa). A densidade de cada grupo variou conforme cada lagoa, sendo, em geral, Asheum sp., Chironomus sp., Beardius sp., Parachironomus sp., Labrundinia sp., Tanytarsus sp., Ablabesmyia sp. e Polypedilum sp. os mais representativos e Limnophyes sp., Denopelopia sp., Paratanytarsus sp. e Parametriocnemus sp. foram os gêneros em menor densidade. O Índice de Dominância variou entre 0,1490 (Lagoa Barbosa em março) e 0,4114 (Lagoa Poço da Pedra em março); e o Índice de Diversidade variaram entre 2,08 (Lagoa Coqueiral em março) e 3,58 (Lagoa Barbosa em agosto) ...
Keywords: Relação inseto-planta; Diptero; Eichhornia; Ecologia aquatica; Ecologia de agua doce; Plantas aquaticas; Proteção ambiental; Diptera